Association between determinants of weight status in children, 13-15 years in Bloemfontein - Meko, Ntsoaki Matumelo Lucia (University of the Free State, 2009)
Introduction: Childhood obesity has become a major public health issue with children being heavier today than they were 20 years ago. This phenomenon is presently observed in both developed and developing countries. As a result of this childhood obesity epidemic, a number of chronic illnesses and risk factors for adult diseases are now beginning in childhood. Most studies conducted in South Africa only determined the prevalence of overweight and obesity, however few addressed the determinants of overweight and obesity in children. Objective: The main objective of this study was to determine the school environment as well as associations between dietary intake, socio-economic status, physical activity levels and weight status of children aged 13 – 15 years in Bloemfontein. Methodology: A representative sample of 415 children of different ethnic and socio-economic backgrounds participated in the study. Questionnaires were used to collect socio-economic, dietary intake, physical activity, and school environment data. Body mass index was calculated using weight and height measurements and waist circumference was measured. The quantitative food frequency questionnaire was used to determine dietary intake, and nutrient intake was analysed. Results: Weight status: Only a small percentage of the children were overweight and obese, with the girls being more overweight and obese than the boys. A statistically significant association was made between BMI and waist circumference. Socio-economic status: The association between socio-economic status and overweight and obesity was not significant, but the prevalence of overweight and obesity was higher in children with a high socio-economic status and lowest in children with a medium socio-economic status. No statistically significant association could be found between BMI and race. However, white children tended to be more overweight and obese than black and coloured children. School environment: Only a few schools reported having nutrition education programmes or campaigns. In most of these schools, the programmes were run only once a year and mostly by educators and not the learners themselves. None of the schools had vending machines on the school premises, but all schools reported having a tuckshop and/or hawkers on or around the school premises. The sale of healthier options of foods such as yoghurt, milk and whole-wheat bread was reported by few schools, while most schools reported selling less healthy options, including crisps, sweets and carbonated drinks. Dietary intake: Macro- and micronutrient intakes of the children were mostly within the adequate range. Fibre intake was below the requirements in most children and the intakes of calcium, folate and potassium were also below requirements. Most of the children had energy intakes equal to or above the estimated energy requirements. Slightly more boys than girls had energy intakes above the estimated energy requirements. No statistically significant association could be made between energy intake and dietary fat intake and BMI. Physical activity levels: Physical activity levels of the children were mostly moderate to vigorous. During the weekend the number of inactive children increased, and that of the vigorously active children decreased. The inactive group of children consisted of more girls than boys. Underweight children had a significantly higher metabolic equivalent value than the normal and overweight groups. No statistically significant association could be made between total number of television hours and BMI. In the category of children who were classified as moderately and vigorously active, statistically significantly more children were underweight compared to the overweight and the normal weight children during the week. Conclusion: Decreased energy intake and promotion of physical activity levels should form integral parts of any prevention program that focuses on childhood obesity. Childhood obesity prevention programmes require a joint multidisciplinary, multisectoral collaboration in order for them to be successful.

Inleiding: Pediatriese vetsug het ‘n belangrike openbare gesondheidsprobleem geword met kinders wat vandag swaarder weeg as 20 jaar gelede. Hierdie verskynsel kom huidiglik in beide ontwikkelde en ontwikkelende lande voor. ‘n Direkte gevolg van hierdie vetsug ontwikkelende epidemie is dat verskeie chroniese siektes en risikofaktore vir volwasse siektes nou reeds in die kinderjare begin voorkom. Die meeste studies wat in Suid-Afrika uitgevoer is het slegs op die voorkoms van oormassa en vetsug gekonsentreer, terwyl slegs enkeles ook die bepalende faktore wat oormassa en vetsug in kinders veroorsaak, ondersoek het. Doelwit van die studie: Die hoofdoelwit van hierdie studie was om die skoolomgewing te ondersoek en verbande tussen dieetinnames, sosio-ekonomiese status, fisiese aktiwiteitsvlakke en massastatus van kinders tussen 13 – 15 jaar in Bloemfontein te bepaal. Metodologie: ‘n Verteenwoordigende steekproef bestaande uit 415 kinders van verskillende etniese en sosio-ekonomiese agtergronde, het aan die studie deelgeneem. Vraelyste is gebruik om data met betrekking tot sosio-ekonomiese status, voedselinname, fisiese aktiwiteitsvlakke en die skoolomgewing in te samel. Liggaamsmassa-indeks (LMI) is met behulp van massa en lengtemate bereken en die middellyfomtrek is gemeet. Die kwantitatiewe voedselfrekwensievraelys is gebruik om voedselinname te bepaal, en die voedingswaarde-inname is daarvolgens geanaliseer. Resultate: Massastatus: ‘n Relatief klein persentasie van die kinders was oormassa en vetsugtig, met meer meisies wat oormassa en vetsugtig was, as seuns. ‘n Statisties betekenisvolle verband is tussen LMI en middellyfomtrek gevind. Sosio-ekonomiese status Sosio-ekonomiese status was nie betekenisvol met oormassa en vetsug geassosieer nie, maar die voorkoms van oormassa en vetsug was wel hoër in kinders met ‘n hoë sosio-ekonomiese status en die laagste in kinders met ‘n medium sosio-ekonomiese status. Geen statisties betekenisvolle verband is tussen LMI en ras gevind nie, maar meer wit kinders was oormassa en vetsugtig as swart- en kleurlingkinders. Skoolomgewing: Slegs ‘n paar skole het ‘n voedingsopleidingsprogram of –veldtog geraporteer. In die meeste van hierdie skole is die program slegs een maal per jaar aangebied en meestal deur opvoeders en nie deur die leerders self nie. Geen van die skole het outomatiese verkoopsmasjiene op die skoolgronde gehad nie, maar al die skole het ‘n snoepwinkel en/of smouse op, of rondom die skoolgronde gerapporteer. Die verkoop van gesonder voedselopsies, soos jogurt, melk en volgraanbrood, is deur ‘n paar skole gerapporteer, terwyl die meeste skole gerapporteer het dat minder gesonde opsies, insluitende skyfies, lekkergoed en gaskoeldrank, verkoop word. Dieetinname: Makro- en mikrovoedingstofinnames van die kinders was meestal binne die aanbevole parameters van toereikendheid. Veselinname van die meeste kinders was laer as die aanbevelings, terwyl die inname van kalsium, folaat en kalium ook laer as toereikend was. Ietwat meer seuns as meisies het energie-innames bo die aanbevole geskatte energievereistes gehad. Geen statisties betekenisvolle verband kon tussen energie-innames en dieetvetinnames of LMI getrek word nie. Fisiese aktiwiteit: Fisiese aktiwiteit van die kinders was meestal matig tot hoog. Meer kinders was oor naweke onaktief as gedurende die week. Die onaktiewe groep kinders het uit meer meisies as seuns bestaan. Dié kinders wat ondermassa was, het ‘n betekenisvol hoër metabolies ekwivalente waarde getoon as dié normale en oormassagroepe. Geen statisties betekenisvolle verband kon tussen die totale aantal ure wat die kinders televisie gekyk het en hul LMI getrek word nie. In die kategorie van kinders wat as matig tot hoogs aktief gedurende die week geklassifiseer is, was statisties betekenisvol meer kinders ondermassa, vergeleke met kinder swat oormassa en normale massa was. Gevolgtrekking: Verminderde energie-inname en bevordering van fisiese aktiwiteitsvlakke behoort integrale dele van enige voorkomingsprogram wat op pediatriese vetsug fokus, te wees. Ten einde suksesvol te wees, sal sodanige programme gesamentlike multidissiplinêre, multisektorale samewerking vereis.
Thesis (Ph.D. (Dietetics))--University of the Free State, 2009
Keywords: Overweight; Obesity; Socio-economic status; Energy intake; Fat intake; Physical activity; School environment; Waist circumference; Body mass index; Teenagers -- Health and hygiene; Obesity -- Teenagers -- Social aspects -- South Africa -- Bloemfontein; Overweight teenagers -- Social aspects -- South Africa -- Bloemfontein